Handbook of Zoology/ Handbuch der Zoologie, Comparative Anatomy of the Gastrointestinal Tract in Eutheria I A Natural History of the Phyla of the Animal Kingdom / Eine Naturgeschichte der Stämme des Tierreiches / Taxonomy, Biogeography and Food: Afrotheria, Xenarthra and Euarchontoglires - Langer, Peter (De Gruyter, 2017)
This volume of the series Handbook of Zoology deals with the anatomy of the gastrointestinal digestive tract – stomach, small intestine, caecum and colon – in all eutherian orders and suborders. It presents compilations of anatomical studies